Immunohistochemical Evaluation of Angiogenesis and Cell Proliferation in Tongue Squamous Cell Carcinoma - Maryam Khalili; Nazanin Mahdavi; Razieh Beheshti; Fereshteh Baghai Naini (Tehran University of Medical Sciences, 2016)
Objectives: Squamous cell carcinoma (SCC) is the most common malignant neoplasm of the oral cavity and a public health threat. Tumor progression is believed to be influenced by angiogenesis as well as tumor cell proliferation; however, the correlation of these two factors in tongue SCC still remains unclear. This study aimed to assess the correlation of these two factors in tongue SCC. Materials and Methods: Twenty-four paraffin block sections of tongue SCC were stained with monoclonal antibodies against CD105 and Ki-67. In order to assess the expressions of CD105 and Ki-67 to evaluate CD105 microvessel density (MVD), positively stained microvessels were counted in a predominantly vascular area (hot spot) in each specimen at ×400 magnification. The proliferation index was expressed as a percentage of Ki-67 positive cells. Data were analyzed by t-test and Pearson's correlation coefficient (P<0.05). Results: The CD105 MVD was related to histological grading as well as Ki67 labeling index (LI; P= 0.045 and P=0.047, respectively). Both CD105 MVD and KI67 LI were unrelated to sex (P=0.41 and P=0.78, respectively) and age (P=0.20 and P=0.36, respectively) of the patients. No correlation was found between CD105 MVD and Ki67 LI (P=0.86). Conclusion: The mean CD105 MVD was significantly lower in poorly differentiated tumors. This finding suggests that CD105 MVD may serve as a valuable prognostic factor in tongue SCC. Absence of correlation between MVD and tumor cell proliferation indicates that these processes may be guided by unrelated mechanisms.